Analisis Hubungan Pencegahan Korupsi dan Pajak Daerah di Indonesia Tahun 2018-2020 - Wibisono, Erfan; Khoirunurrofik, Khoirunurrofik (Jurnal Kebijakan Ekonomi, 2023)
Regional autonomy aims to improve the regional economy in order to create a just and prosperous society. However, the reality is that until now the local government still depends on transfer funds from the Central Government. KPK, through the Monitoring Center for Prevention (MCP) program, known as the corruption prevention system, seeks to enable local governments to increase local taxes. The method used is multiple linear regression with a fixed effect. The results of the study show that the Corruption Prevention System, which is represented by the MCP score, has a positive and significant relationship with local tax revenues. This shows the importance of a corruption prevention system in all local governments by implementing good corporate governance